BATASAN MENGAMBIL KEUNTUNGAN MENURUT HUKUM ISLAM - Nasution, Adanan Murroh (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2018)
Humans are creatures of God who have the character and nature of mutual need between one another. This is what is called muamalah. No one can have everything he wants without the help of others. For this reason, God inspired them to trade trades and everything that would be beneficial, one of them by buying and selling.The Islamic Shari'a encourages people to trade and advocates it as a way to gather fortune, because Islam recognizes procdutivity because Islam is the last religion that has been perfect and is universal, applies to all humans, all nations and the substance of their teachings brings the goodness of life. In addition, Islam is also an eternal religion (valid from one era to the next) until the Day of Judgment. Islamic teachings regulate all aspects of human life including about trading or doing business even to the procedure for taking legitimate profits.